2016
DOI: 10.5194/se-2016-54
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the path to the digital rock physics of gas hydrate bearing sediments – processing of in-situ synchrotron-tomography data

Abstract: Abstract. To date, very little is known about the distribution of gas hydrates in sedimentary matrices and the resulting matrix-pore network affecting the seismic properties at low hydrate concentration. Digital rock physics offers a unique solution to this issue yet requires good quality, high resolution 3D representations for the accurate modelling of petrophysical and transport properties. Although such models are readily available via in-situ synchrotron radiation X-ray tomography the analysis of such data… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The methane hydrate distribution in the reservoir sediment is complicated. The laboratory observation identified various hydrate distributions, including grain-coating, pore-filling, bridging and matrix-supporting [43,44]. The typical hydrate distributions comprising pore-filling (hydrate occupies pore centers) and grain-coating (hydrate coats the sediment matrix) were commonly used to analyze the effect of the hydrate sediment structures on the permeability in previous pore-scale studies [45][46][47] .…”
Section: Physical Problemmentioning
confidence: 99%
“…The methane hydrate distribution in the reservoir sediment is complicated. The laboratory observation identified various hydrate distributions, including grain-coating, pore-filling, bridging and matrix-supporting [43,44]. The typical hydrate distributions comprising pore-filling (hydrate occupies pore centers) and grain-coating (hydrate coats the sediment matrix) were commonly used to analyze the effect of the hydrate sediment structures on the permeability in previous pore-scale studies [45][46][47] .…”
Section: Physical Problemmentioning
confidence: 99%
“…X‐ray computed tomography (CT) is also nondestructive and can yield 3‐D images of the inner structure of both pressure cores and laboratory specimens during hydrate formation and dissociation (Han et al, ; Kneafsey et al, ; Lee et al, ; Sato et al, ; Rees et al, ; Yun et al, ). Especially, microfocus CT facilitates the study of hydrate pore habits with a resolution of tens of microns to submicrons (Sell et al, ). However, one of the major challenges of this technique is to distinguish the hydrate phase from the water phase due to their similar attenuation coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on high-quality tomography (e.g., micro-computed tomography and X-ray tomography), it is reported that pore-filling type MH is formed even in the free gas environment[52]. Moreover, reliable evidences that the transformation of MH morphology and coexistence of different MH morphologies are increasingly reported[53,54]. Therefore, cautions should be taken when using experimental data in terms of MH morphology since idealized pore-filling or cementation type MH may not physically exist.The effect of MH morphology is not accounted for in this study because available experiments are not sufficient to isolate the effects of pore-filling, cementation, grain-coating, and load-bearing types of MH.…”
mentioning
confidence: 99%